An iodinated polydiacetylene liposome nano-preparation and a preparation method thereof
Patent Information
- Application Number
- CN202611335409.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-09
AI Technical Summary
然而,将PIDA制备为均一、稳定的纳米粒子面临多重技术障碍
(1)本发明针对碘代聚二炔PIDA材料因高度疏水、分子链刚性强、链间π-π堆积作用显著而难以被制备为纳米制剂的固有缺陷,提出了一条“模板拓扑排列—液氮脆断研磨—光照聚合”的PIDA短纤维制备方法。该制备方法中,液氮脆断研磨在聚合前进行,有效避免了长链PIDA纤维因分子链间强π-π堆积作用而难以破碎的制剂学难题;光照聚合在研磨后进行,使PIDA纤维长度可控、分布均一。在此基础上以脂质体为载体进行包载,实现了PIDA材料的纳米制剂化。
Smart Images

Figure CN122874609A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomedicine technology, and more specifically, relates to an iodopolydiyne liposome nanoformulation and its preparation method. Background Technology
[0002] Nanoparticles, as an important drug delivery system, have been widely used in fields such as targeted cancer therapy, biomedical imaging, and disease diagnosis. By encapsulating drugs or imaging agents in carriers such as liposomes and polymer nanoparticles, their in vivo distribution can be significantly improved, circulation time prolonged, and toxic side effects reduced, making it a core technology in modern pharmaceutics.
[0003] Polydiiododiacetylene (PIDA) is a novel type of conjugated polymer material. Its main chain consists of alternating carbon-carbon single, double, and triple bonds, while its side chains contain a large number of iodine atoms. It exhibits excellent CT imaging performance and characteristic Raman signals, making it potentially valuable for applications in biomedical imaging. However, preparing uniform and stable nanoparticles from PIDA faces several technical obstacles. First, the conjugated main chain of PIDA exhibits extremely strong intermolecular π-π stacking interactions, making it highly hydrophobic and insoluble in water and common injectable solvents, hindering the direct preparation of nanoparticles using conventional nanoprecipitation or self-assembly methods. Second, conventional PIDA consists of long, rigid fiber chains with complex inter-chain interactions. Conventional top-down physical dispersion methods (such as ultrasound) are insufficient to process it into uniformly sized nanoparticles, leading to easy aggregation and precipitation, which fails to meet the particle size and stability requirements of injectable nanoparticle formulations. Third, as a novel imaging material, the practical application value of PIDA depends on whether it can obtain nano-formulations with uniform particle size and stable dispersion. If the dispersion stability problem cannot be effectively solved, the material will not be able to be further adapted to subsequent formulation processes such as liposome encapsulation.
[0004] Therefore, although PIDA materials possess the aforementioned excellent properties, these properties cannot be transformed into practical application value unless the problem of nanoparticle preparation is first solved.
[0005] To address the aforementioned issues, there is an urgent need to establish a method for preparing hydrophobic PIDA materials into nano-formulations with uniform particle size and stable dispersion. Summary of the Invention
[0006] In view of the above-mentioned defects or improvement needs of the existing technology, the present invention provides an iodopolydiyne liposome nanoparticle formulation and its preparation method. The purpose is to solve the technical problem that iodopolydiyne fiber materials are difficult to prepare into nanoparticles with uniform particle size and stable dispersion due to their high hydrophobicity, strong molecular chain rigidity, and significant inter-chain π-π stacking effect.
[0007] According to a first aspect of the present invention, a method for preparing iodopolydiyne liposome nanoparticles is provided, comprising the following steps: (1) The iodopolydiyne monomer is arranged into a eutectic by template topological polymerization to obtain a monomer eutectic; the monomer eutectic is immersed in liquid nitrogen and then taken out and ground in the dark to obtain monomer crystal powder; the monomer crystal powder is subjected to photopolymerization to obtain iodopolydiyne fiber; (2) The iodopolydiyne fiber obtained in step (1) is added to the liposome suspension for dispersion. The iodopolydiyne fiber is loaded in the liposome carrier to obtain iodopolydiyne liposome nanoformulation.
[0008] Preferably, the eutectic alignment time is 96 h-144 h.
[0009] Preferably, the soaking time is 5 min to 10 min.
[0010] Preferably, the photopolymerization time is 10 min to 30 min.
[0011] Preferably, the liposome suspension is prepared by the following method: dissolving lecithin and cholesterol in an organic solvent and rotary evaporating to form a lipid film; adding an hydration solution to the lipid film for hydration to obtain the liposome suspension.
[0012] Preferably, the mass ratio of the iodopolydiyne fiber, lecithin and cholesterol is 1:(3~7):1.
[0013] Preferably, the iodopolydiyne liposome nanoformulation is freeze-dried to obtain freeze-dried iodopolydiyne liposome nanoformulation.
[0014] Preferably, after dispersion, the template is removed by methanol elution.
[0015] Preferably, the elution is performed 2-5 times.
[0016] According to another aspect of the present invention, an iodopolydiyne liposome nanoformulation prepared therefrom is provided.
[0017] In summary, compared with the prior art, the above-described technical solutions conceived by this invention mainly possess the following technical advantages: (1) This invention addresses the inherent limitations of iodopolydiyne (PIDA) materials, which are difficult to prepare into nano-formulations due to their high hydrophobicity, strong molecular chain rigidity, and significant inter-chain π-π stacking interactions. It proposes a method for preparing short PIDA fibers using a process of "template topological arrangement—liquid nitrogen brittle-breaking grinding—photopolymerization." In this method, liquid nitrogen brittle-breaking grinding is performed before polymerization, effectively avoiding the formulation problem of long-chain PIDA fibers being difficult to break due to strong inter-chain π-π stacking interactions. Photopolymerization is performed after grinding, ensuring controllable PIDA fiber length and uniform distribution. Based on this, liposomes are used as carriers for encapsulation, realizing the nano-formulation of PIDA materials.
[0018] (2) Through systematic formulation screening, this invention clarifies the influence of the mass ratio of PIDA material, lecithin and cholesterol on the particle size, distribution and stability of the formulation. Preferably, the mass ratio of iodopolydiyne monomer, lecithin and cholesterol is 1:(3~7):1, which realizes the precise control of the particle size of the nano-formulation (165±15 nm, PDI<0.3) and solves the key technical problems of particle size uniformity and dispersion stability of PIDA nano-formulation.
[0019] (3) The PIDA liposome nano-formulation prepared by the present invention showed no significant change in particle size within 6 months under storage conditions at 4℃, maintained a polydispersity index below 0.3, and exhibited no aggregation or precipitation, thus demonstrating good long-term storage stability and meeting the stability requirements for injectable nano-formulations.
[0020] (4) The preparation processes used in this invention, such as template topological polymerization, liquid nitrogen brittle fracture grinding, thin film hydration, and ultrasonic dispersion, are mild, easy to operate, and have good repeatability, making them suitable for large-scale production. Preferably, the phospholipids and cholesterol used are FDA-approved pharmaceutical excipients, ensuring biocompatibility and providing feasible formulation solutions for the subsequent application of PIDA materials.
[0021] (5) The PIDA liposome nanoformulation prepared by the preparation method of the present invention has completely preserved the CT imaging performance and Raman signal characteristics of the PIDA material it encapsulates, indicating that the formulation process of the present invention does not damage the functional properties of the PIDA material. Attached Figure Description
[0022] Figure 1 This is a process flow diagram for the preparation of the iodopolydiyne liposome nanoformulation of the present invention.
[0023] Figure 2 This invention describes the topological polymerization preparation process of iodopolydiyne.
[0024] Figure 3 This is a eutectic diagram obtained at different crystallization times for the iodopolydiyne of the present invention.
[0025] Figure 4 This is a comparison chart of the particle size and PDI of short fibers coated with iodopolydiyne obtained under different treatment parameters according to the present invention.
[0026] Figure 5 This is a transmission electron microscope (TEM) image of the iodinated polydiyne liposome nanoformulation of the present invention.
[0027] Figure 6 This is a dynamic light scattering (DLS) particle size distribution diagram of the iodinated polydiyne liposome nanoformulation of the present invention.
[0028] Figure 7 This is a comparison chart of the particle size and stability of nano-formulations with different phospholipid / iodopolydiyne ratios.
[0029] Figure 8 The results show the long-term stability of the iodopolydiyne liposome nanoformulation of this invention under storage conditions at 4°C.
[0030] Figure 9 The energy dispersive spectroscopy (EDS) diagram of the iodinated polydiyne liposome nanoformulation of the present invention shows that the iodine element is uniformly distributed.
[0031] Figure 10 This is the Fourier Transform Infrared (FTIR) spectrum of the iodinated polydiyne liposome nanoformation of the present invention.
[0032] Figure 11 This is the result of the biosafety evaluation of the iodinated polydiyne liposome nanoformulation of the present invention.
[0033] Figure 12 To assess the blood safety of the iodinated polydiyne nanoformulation of this invention. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0035] The first embodiment of the present invention provides a method for preparing iodopolydiyne liposome nanoparticles, comprising the following steps: (1) The iodopolydiyne monomer is arranged in a eutectic arrangement by template topological polymerization to obtain a monomer eutectic; the monomer eutectic is immersed in liquid nitrogen and then taken out and ground in the dark to obtain monomer crystal powder; the monomer crystal powder is subjected to photopolymerization to obtain iodopolydiyne fiber; (2) The iodopolydiyne fiber obtained in step (1) is added to the liposome suspension for dispersion. The iodopolydiyne fiber is loaded in the liposome carrier to obtain iodopolydiyne liposome nanoformulation.
[0036] When PIDA material is pre-formed into an ordered eutectic structure using a template topology, and then subjected to liquid nitrogen embrittlement and grinding treatment, its fiber size is significantly reduced and the intermolecular chain stacking effect is effectively weakened, allowing the polymerized PIDA material to be effectively encapsulated by liposomes. Furthermore, by controlling the mass ratio of PIDA material to the components in the carrier, uniform nanoparticles with a particle size of 150–300 nm can be obtained, exhibiting dispersion and storage stability comparable to injectable nanoparticle formulations.
[0037] This invention employs a template-based topological polymerization method. First, PIDA monomers are induced to align in a crystal lattice template, and then topologically polymerized to obtain a PIDA cocrystal. The cocrystal is then subjected to brittle fracture under liquid nitrogen conditions followed by grinding, which effectively reduces the size of the PIDA fibers and decreases the tight packing between molecular chains. Subsequently, phospholipid / cholesterol liposomes are used as carriers for encapsulation, and ultrasonic dispersion is applied to prepare PIDA liposome nanoparticles with uniform particle size and stable dispersion. The key to this technical approach lies in: pre-constructing an ordered conjugated structure through template-based topological polymerization, followed by effective deaggregation of PIDA through liquid nitrogen brittle fracture and grinding, thus creating the necessary conditions for subsequent liposome encapsulation.
[0038] Unlike conventional liposome-encapsulated small molecule drugs, the key to the preparation method described in this invention lies in the preparation route of PIDA short fibers, which adopts the sequence of "template arrangement—liquid nitrogen brittle fracture grinding—photopolymerization": First, template topological polymerization is used to arrange monomers regularly and crystallize them to form a eutectic structure. At this point, the eutectic structure is complete and has not yet undergone spontaneous polymerization. After liquid nitrogen brittle fracture and grinding, the eutectic is broken into uniform fine crystalline powder. Finally, photopolymerization is performed to obtain PIDA short fibers. In this route, liquid nitrogen brittle fracture grinding is performed before polymerization, effectively avoiding the formulation problem of long-chain PIDA fibers being difficult to break due to strong π-π stacking between molecular chains. At the same time, photopolymerization is performed after grinding to ensure that the fiber length is moderate and the distribution is uniform. The PIDA short fibers prepared by the above steps can be efficiently encapsulated by liposomes to form nano-formulations with uniform particle size and stable dispersion.
[0039] In some embodiments, the eutectic alignment time is 96 h-144 h. If the crystallization time is insufficient (<72 h), the eutectic is incomplete; if the crystallization time is too long (>168 h), the eutectic has already begun to self-polymerize. In some embodiments, the soaking time is 5 to 10 minutes.
[0040] In some embodiments, the photopolymerization time is 10 to 30 minutes.
[0041] In some embodiments, the liposome suspension is prepared by dissolving lecithin and cholesterol in an organic solvent and rotary evaporating to form a lipid film; adding an hydration solution to the lipid film for hydration to obtain the liposome suspension.
[0042] Preferably, the organic solvent is dichloromethane; the hydration solution is pure water or phosphate buffer.
[0043] In some embodiments, the mass ratio of iodopolydiyne monomer, lecithin, and cholesterol is 1:(3~7):1.
[0044] In some embodiments, the iodopolydiyne liposome nanoformulation is freeze-dried to obtain the freeze-dried iodopolydiyne liposome nanoformulation.
[0045] In some embodiments, the template is removed by elution with methanol after dispersion; Preferably, the number of washes is 2-5.
[0046] In some embodiments, dispersion is performed using ultrasonic dispersion, with a dispersion time of 2-5 hours.
[0047] In some embodiments, a step of uniformizing particle size by extrusion or filtration is also included.
[0048] The second embodiment of the present invention provides an iodopolydiyne liposome nanoformulation.
[0049] In some embodiments, the liposome nanoformulation includes a liposome carrier and an iodopolydiyne material encapsulated therein, wherein the liposome carrier is preferably composed of phospholipids and cholesterol, and the particle size of the nanoformulation is 150-300 nm.
[0050] In some embodiments, the nanoparticles have a particle size of 165±15 nm and a polydispersity index of less than 0.3.
[0051] In some embodiments, the zeta potential of the nanoformulation is -35 to -55 mV.
[0052] The technical effects of the present invention will be further illustrated below with reference to the embodiments.
[0053] Example 1: Preparation of iodopolydiyne (PIDA) lipid nanoparticles (1) Preparation of iodopolydiyne short fibers Iodinated polydiyne monomers were arranged in a regular pattern via template topological polymerization and crystallized at 4°C for 6 days to obtain a monomer eutectic. The iodinated polydiyne monomers and template molecules were dissolved in methanol at a specific molar ratio. The template molecules self-assembled into a two-dimensional network structure through hydrogen bonds between amide groups; simultaneously, the iodine atoms at the ends of the monomer molecules interacted with the cyano (or pyridyl) nitrogen atoms at the ends of the template molecules through halogen bonds. Under the synergistic effect of hydrogen and halogen bonds, the monomer molecules arranged in a regular spatial pattern guided by the template. The solution was then allowed to crystallize at 4°C for 6 days to allow for complete co-crystallization of the monomer and template, forming an ordered host-guest eutectic structure. The eutectic initially appeared light blue.
[0054] After immersing the obtained eutectic in liquid nitrogen for 5 minutes, remove it and grind it rapidly for 30 minutes in the dark to obtain fine crystalline powder of the monomer (the key to liquid nitrogen brittle fracture is to make the eutectic brittle and hard at low temperature, so that it is easy to grind and break; if the grinding time is too short, the particles will be coarse and the fibers obtained by subsequent polymerization will be too long; if the grinding time is too long, the crystal structure may be excessively destroyed).
[0055] The fine crystalline powder of the monomer was photopolymerized under a fluorescent lamp for 20 minutes to obtain iodopolydiyne eutectic (photopolymerization was carried out after grinding, so that the fiber length could be controlled and the distribution was uniform, avoiding the problem of breaking after polymerization). Figure 2 This invention describes the topological polymerization process for preparing iodopolydiyne. The template was removed by elution with methanol three times, the product was collected by centrifugation, and dried to obtain purified iodopolydiyne short fibers.
[0056] (2) Preparation of liposomes Lecithin and cholesterol were dissolved in dichloromethane at a mass ratio of 5:1, and the mixture was rotary evaporated at 35°C until a uniform lipid film was formed. The film was then vacuum dried overnight. Pure water was added to the lipid film, and the mixture was hydrated at 35°C for 30 minutes to obtain a liposome suspension.
[0057] (3) Assembly of PIDA liposome nanoformulation The iodopolydiyne short fibers obtained in step (1) were added to the liposome suspension obtained in step (2) to make the mass ratio of PIDA to lecithin 1:5. The mixture was ultrasonically dispersed for 4 hours (power 200 W, frequency 40 kHz) to obtain PIDA liposome nanoformulation.
[0058] The technical challenge of this embodiment lies in the fact that PIDA material, after polymerization, exhibits a long fibrous morphology with extremely strong π-π stacking interactions between molecular chains. If polymerization is performed first followed by physical fragmentation, it is impossible to obtain uniform short fibers, which are also difficult to be effectively encapsulated by liposomes. This invention effectively solves the above-mentioned problems by following the sequence of "template arrangement—liquid nitrogen brittle fracture grinding—photopolymerization". Figure 1This is a process flow diagram of the preparation method described in this embodiment, which sequentially shows the entire process of template topological arrangement, crystallization, liquid nitrogen brittle fracture grinding, photopolymerization, methanol elution, liposome encapsulation, and ultrasonic dispersion.
[0059] Example 2: Screening of key parameters for PIDA short fiber preparation To determine the optimal preparation conditions for PIDA short fibers, single-factor screening was performed on crystallization time, grinding time, photopolymerization time, and methanol elution times. With other conditions fixed, PIDA short fibers were prepared according to the method in Example 1 and further encapsulated in liposomes. The formulation particle size and polydispersity index (PDI) were used as evaluation indicators.
[0060] (1) Screening of crystallization time Crystallization times were set to 72 h, 96 h, 120 h, 144 h, and 168 h, respectively, with a fixed grinding time of 30 minutes, photopolymerization time of 20 minutes, and methanol elution three times.
[0061] The results showed that at 72 h of crystallization, the eutectic was not fully formed, and the fiber length obtained after photopolymerization was uneven. The particle size of the encapsulated formulation was >300 nm and the PDI was >0.4. At 96 h of crystallization, the eutectic was initially formed, and the particle size of the encapsulated formulation was about 220 nm and the PDI was about 0.32. At 120 h of crystallization, the eutectic structure was complete, and the particle size of the encapsulated formulation was the smallest (about 165 nm) and the most uniform (PDI <0.2). At 144 h of crystallization, the particle size of the encapsulated formulation was about 185 nm and the PDI was about 0.25. At 168 h of crystallization, some monomers had begun to spontaneously polymerize, and a small number of long fiber aggregates appeared in the encapsulated formulation with a particle size >250 nm and a PDI >0.35. Figure 3 This is a eutectic diagram obtained at different crystallization times for the iodopolydiyne of the present invention.
[0062] The above results indicate that a crystallization time of 96–144 h is the preferred range, with 144 h being the optimal crystallization time. Insufficient crystallization time (<72 h) results in incomplete eutectic, while excessive crystallization time (>168 h) indicates that the eutectic has begun to spontaneously polymerize, both of which are detrimental to subsequent liposome encapsulation.
[0063] (2) Selection of grinding time The grinding time was set to 10 minutes, 20 minutes, 30 minutes, 40 minutes and 50 minutes respectively, the crystallization time was fixed for 5 days, the photopolymerization time was 20 minutes, and the methanol elution was performed 3 times.
[0064] The results showed that after 10 minutes of grinding, the eutectic was not sufficiently broken down, resulting in large particles with a particle size of approximately 280 nm and a PDI > 0.38 after encapsulation. After 20 minutes of grinding, the particle size of the encapsulated formulation was approximately 195 nm, with a PDI of approximately 0.28. After 30 minutes of grinding, the encapsulated formulation had the smallest particle size (approximately 165 nm) and the most uniform distribution (PDI < 0.2). After 40 minutes of grinding, the particle size of the encapsulated formulation was approximately 170 nm, with a PDI of approximately 0.22. After 50 minutes of grinding, the particle size of the encapsulated formulation increased slightly (approximately 185 nm), with a PDI of approximately 0.26, possibly due to the introduction of impurities or partial destruction of the crystal structure caused by excessive grinding. Figure 4 This is a comparison chart of the particle size and PDI of short fibers coated with iodopolydiyne obtained under different treatment parameters according to the present invention.
[0065] The above results indicate that a grinding time of 20-40 minutes is the preferred range, with 30 minutes being the optimal grinding time. Insufficient grinding results in coarse particles that cannot be effectively encapsulated by liposomes; excessive grinding may affect the material properties.
[0066] (3) Screening of photopolymerization time The photopolymerization time was set to 5 minutes, 10 minutes, 20 minutes, 30 minutes and 40 minutes respectively, the crystallization time was fixed at 5 days, the grinding time was 30 minutes and the methanol elution was performed 3 times.
[0067] The results showed that: when exposed to light for 5 minutes, polymerization was incomplete, the yield of PIDA short fibers was low, and the intensity of CT and Raman signals after loading was insufficient; when exposed to light for 10-30 minutes, polymerization was complete, the particle size of the loaded formulation was uniform (PDI<0.25), and the signal intensity met the requirements, with 20 minutes being the optimal time; when exposed to light for 40 minutes, the fibers grew excessively, and the length of some fibers in the loaded formulation increased, and the particle size distribution became wider (PDI>0.35).
[0068] The above results indicate that a photopolymerization time of 10–30 minutes is the preferred range, with 20 minutes being the optimal illumination time. Too short an illumination time results in incomplete polymerization and insufficient signal intensity; too long an illumination time leads to excessive fiber growth, affecting particle size uniformity.
[0069] (4) Screening of methanol elution times The methanol elution times were set to 1, 2, 3, 4, and 5 times, respectively, and the crystallization time was fixed at 5 days, the grinding time at 30 minutes, and the photopolymerization time at 20 minutes.
[0070] The results showed that when eluted once, the template residue was obvious (the characteristic absorption peak of the template could be seen by FTIR detection), which affected the purity and biosafety of the material; when eluted 2 to 3 times, the template was completely removed, and the purification requirements could be met in 3 times; when eluted 4 to 5 times, the purification effect was comparable to that of 3 times, but the operation steps increased and the material loss increased.
[0071] The above results indicate that elution with methanol for 2 to 5 times is the preferred range, with 3 times being the optimal number of elutions, which can ensure complete removal of the template while maintaining operational efficiency.
[0072] (1) Particle size and potential: The average particle size of the nano-formulation was 165 nm, the polydispersity index (PDI) was less than 0.2, and the zeta potential was about -45 mV, as determined by dynamic light scattering (DLS). Transmission electron microscopy (TEM) showed that the nano-formulation was uniformly spherical, well dispersed, and without aggregation. Figure 5 This is a transmission electron microscope (TEM) image of the iodinated polydiyne liposome nanoformulation of the present invention. Figure 6 This is a dynamic light scattering (DLS) particle size distribution diagram of the iodinated polydiyne liposome nanoformulation of the present invention.
[0073] (2) Stability test: The nano-formulation was stored at 4°C for 6 months, and samples were taken at 1, 2, 3 and 6 months to determine the particle size and PDI. The results showed that the particle size did not change significantly within 6 months, the PDI remained below 0.3, and there was no aggregation or precipitation, indicating that the formulation has good long-term storage stability. Figure 7 This is a comparison chart of particle size and stability of nano-formulations with different phospholipid / iodopolydiyne ratios. Figure 8 The results show the long-term stability of the iodopolydiyne liposome nanoformulation of this invention under storage conditions at 4°C.
[0074] (3) Energy dispersive spectroscopy (EDS): EDS elemental analysis of the nano-formulation confirmed that iodine was uniformly distributed in the nanoparticles. Figure 9 The energy dispersive spectroscopy (EDS) diagram of the iodinated polydiyne liposome nanoformulation of the present invention shows that the iodine element is uniformly distributed.
[0075] (4) FTIR spectroscopy: FTIR analysis of the PIDA liposome nanoformulation showed no template characteristic absorption peak, proving that the template in PIDA was completely removed; at the same time, the characteristic absorption peak of the liposome carrier (approximately 1735 cm⁻¹) was visible. - The peak at ¹ represents the C=O stretching vibration of the carbonyl group in phospholipid esters, approximately 1100 cm⁻¹. - The peak at position ¹ represents the stretching vibration peak of the COC bond, confirming the effective encapsulation of PIDA by liposomes. Figure 10 This is the Fourier Transform Infrared (FTIR) spectrum of the iodinated polydiyne liposome nanoformation of the present invention.
[0076] Example 3: Screening of different phospholipid / PIDA ratios PIDA short fibers were prepared according to the method in Example 1 and further encapsulated in liposomes. Nanoformations with phospholipid / PIDA mass ratios of 3:1, 4:1, 5:1, 6:1, and 7:1 were prepared, and the effects of different ratios on particle size, PDI, and stability were investigated.
[0077] The results showed that at ratios of 3:1 and 4:1, the nanoparticle size was relatively large (>220 nm) and unevenly distributed (PDI>0.3), with some samples showing precipitation; at a ratio of 5:1, the nanoparticle size was the smallest (approximately 165 nm), the distribution was the most uniform (PDI<0.2), and the stability was the best; at ratios of 6:1 and 7:1, the nanoparticle size increased slightly (approximately 180 nm), the stability was similar to that of the 5:1 ratio, but the drug loading was relatively low.
[0078] Considering factors such as particle size, distribution uniformity, stability, and drug loading, a mass ratio of 1:5 for PIDA to lecithin was determined to be the optimal ratio.
[0079] Example 4: In vitro performance verification of PIDA liposome nanoformulation The liposome nanoformulation prepared in Example 1 was subjected to in vitro performance verification, and the results are as follows: (1) Naked-eye recognition capability: The PIDA liposome nanoparticle suspension is uniformly deep blue and can be clearly distinguished by the naked eye. The ultraviolet-visible absorption spectrum shows a characteristic broad absorption peak at 600~700 nm.
[0080] (2) CT imaging performance: PIDA liposome nanoparticles at different concentrations (0.5~20 mg / mL) were subjected to CT scans (70 kV). The CT value increased linearly with the concentration (R²>0.99), and the CT value reached 917 HU at 20 mg / mL.
[0081] (3) Raman spectroscopy performance: Under 785 nm laser excitation, PIDA liposome nanoparticles exhibit Raman spectroscopy performance at 2078 cm⁻¹. - A characteristic Raman peak is observed at point ¹, with a signal-to-noise ratio >10.
[0082] Example 5: Biosafety Evaluation The liposome nanoformulation prepared in Example 1 was subjected to a biosafety evaluation, and the results are as follows: (1) Cytotoxicity: When PIDA liposome nanoparticles were co-cultured with macrophages THP-1, human normal hepatocytes L-O2, human renal proximal tubular epithelial cells HK-2 and human embryonic kidney cells HEK-293T for 2 days, the cell survival rate was >85% in the concentration range of 1~20 μg / mL, and no cytotoxicity was observed.
[0083] (2) Hemolysis test: The probe concentration of 20~100 μg / mL was incubated with red blood cells for 1 h and 2 h respectively. The hemolysis rate was <5%, which meets the requirements of GB / T 16886. Figure 11 This is the result of the biosafety evaluation of the iodinated polydiyne liposome nanoformulation of the present invention.
[0084] (3) In vivo safety: Blood samples were collected from New Zealand rabbits 3 days after injection of PIDA liposome nanoparticles (300 μL, 20 mg / mL). Blood routine (WBC, RBC, PLT, HGB) and blood biochemistry (ALT, AST, BUN, CREA) indicators were all within the normal range. One day after injection, heart, liver, spleen, lung and kidney samples were collected for H&E staining. No obvious inflammatory cell infiltration, necrosis or fibrosis was observed. Figure 12 To assess the blood safety of the iodinated polydiyne nanoformulation of this invention.
[0085] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing an iodopolydiyne liposome nanoparticle formulation, characterized in that, Includes the following steps: (1) The iodopolydiyne monomer is arranged into a eutectic by template topological polymerization to obtain a monomer eutectic; the monomer eutectic is immersed in liquid nitrogen and then taken out and ground in the dark to obtain monomer crystal powder; the monomer crystal powder is subjected to photopolymerization to obtain iodopolydiyne fiber; (2) The iodopolydiyne fiber obtained in step (1) is added to the liposome suspension for dispersion. The iodopolydiyne fiber is loaded in the liposome carrier to obtain iodopolydiyne liposome nanoformulation.
2. The method for preparing the iodopolydiyne liposome nanoparticle formulation as described in claim 1, characterized in that, The eutectic alignment time is 96 h-144 h.
3. The method for preparing the iodopolydiyne liposome nanoparticle formulation as described in claim 1, characterized in that, The soaking time is 5 min-10 min.
4. The method for preparing the iodopolydiyne liposome nanoparticle formulation as described in claim 1, characterized in that, The photopolymerization time is 10 min-30 min.
5. The method for preparing iodopolydiyne liposome nanoparticles according to any one of claims 1-4, characterized in that, The liposome suspension is prepared by the following method: lecithin and cholesterol are dissolved in an organic solvent and rotary evaporated to form a lipid film; an hydration solution is added to the lipid film for hydration to obtain the liposome suspension.
6. The method for preparing iodopolydiyne liposome nanoparticles as described in claim 5, characterized in that, The mass ratio of the iodopolydiyne fiber, lecithin and cholesterol is 1:(3~7):
1.
7. The method for preparing iodopolydiyne liposome nanoparticles as described in claim 1, characterized in that, The iodopolydiyne liposome nanoformulation was freeze-dried to obtain freeze-dried iodopolydiyne liposome nanoformulation.
8. The method for preparing iodopolydiyne liposome nanoparticles as described in claim 1, characterized in that, After dispersion, the template is removed by methanol elution.
9. The method for preparing iodopolydiyne liposome nanoparticles as described in claim 8, characterized in that, The number of washes is 2-5.
10. Iodinated polydiyne liposome nanoformulations prepared by any one of claims 1-9.